2011
DOI: 10.1515/polyeng.2011.070
|View full text |Cite
|
Sign up to set email alerts
|

Dilute solution viscometry study on the miscibility of N,O-carboxymethyl chitosan-cellulose acetate blends

Abstract: Dilute solution viscometry method is used for studying viscosity behavior of newly prepared N , O -carboxymethyl chitosan (NOCC), cellulose acetate (CA), and their blends at different compositions (0/10, 2/8, 4/6, 5/5, 6/4, 8/2, 10/0). In this method, reduced viscosity ( η sp / c ) and inherent viscosity (ln η rel / c ) of the given polymer sample have been determined by measuring the fl ow time of the polymer sample in acetone solvent. Huggins ( k ) and Kraemer coeffi cients ( k ′ ) for given polymer-solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Among these polymer blends, chitosan/cellulose blend is one of the most promising materials because of the abundance of cellulose and chitin which is parent polymer of chitosan. Numerous investigations have been carried out about chitosan/cellulose blends, which seem to be proper to prepare antibacterial Lyocell fibers [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among these polymer blends, chitosan/cellulose blend is one of the most promising materials because of the abundance of cellulose and chitin which is parent polymer of chitosan. Numerous investigations have been carried out about chitosan/cellulose blends, which seem to be proper to prepare antibacterial Lyocell fibers [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additive or even synergistic effects can render the performance of CTS membrane more functional. For example, separation performance of the CA membrane can be increased by blending N,O-carboxymethyl chitosan and CA; 28,29 also, antibacterial properties of cyanoethylchitosan/CA polymer blended membrane has been improved. 27 It has been demonstrated that the existence of inorganic segments could enhance the chemical stability, thermal tolerance, and mechanical properties, and tune the microstructure and Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, additive or even synergistic effects can render the performance of CTS membrane more functional. For example, separation performance of the CA membrane can be increased by blending N , O ‐carboxymethyl chitosan and CA; also, antibacterial properties of cyanoethylchitosan/CA polymer blended membrane has been improved …”
Section: Introductionmentioning
confidence: 99%